Trend vývoja železničných staníc - Dubeňová, Ľubica (Akademické nakladatelství CERM, 2013)
Dating back to the 1830s, railways were developed in Britain. The history of railway stations began with a transit station in which the reception area and the hall were separate buildings. This division of stations into two buildings, of which one is primarily representative and the other serves for engineering purposes remained the only architectural option for a long time and has not disappeared to this day. Soon after, they became a major mode of public transportation in many places across the world and served communities. Passenger stations became a new building type and gateways to rail lines connecting cities. Railway stations entered a new age again in the late 20th century after the introduction of high-speed trains. As evident mostly in Europe (and of course China), many new stations were built, and the old ones were renovated to efficiently serve the system. Once different transportation modes were unconnected, but today the trend is towards an integrated system. Many railway stations form an interchange between modes of transportation that may include buses, air services, metros, taxi, private cars, and so forth. Therefore the intermodal concept reflects a new form of service. In addition to serving intercity rail lines, the concept emphasizes linkages to other transportation systems, the expansion of service across borders, and rail networks linking cities and their suburbs. As a consequence, new forms of station type are required. International, airport, and metro or light rail stations represent different types emerging as distinctive building patterns for railway stations impacted by the intermodal concept.

Súčasný rozvoj železničnej dopravy má snahu zabezpečiť rovnováhu medzi súkromnou a verejnou formou dopravy, medzi vnútromestskými cestami a prepojením spádového územia s mestom. Cestujúci strávia množstvo času pri svojich presunoch za prácou, domovom, služobnou cestou, atď., a preto je potrebné im vytvoriť vhodné prostredie na túto aktivitu. Pre moderného človeka práve čas zohráva dôležitú úlohu pri jeho cestovaní. Chce sa presúvať na miesto určenia v čo najkratšom čase a ak už má niekde čakať na ďalší spoj, chce byť v kultúrnom, čistom prostredí, kde by poprípade mohol využívať aj služby pre verejnosť, napr. kaviareň, reštauráciu, obchody, atď.
The development trend of railway stations
Keywords: železniční stanice; veřejná doprava; vysokorychlostní vlaky; integrovaný systém; intermodální koncepce; railway stations; public transport; high-speed trains; integrated system; intermodal concept